Anatomy of a twin DNA replication factory - Li, Huilin (Biochem Soc Trans, 2020)
The replication of DNA in chromosomes is initiated at sequences called origins at which two replisome machines are assembled at replication forks that move in opposite directions. Interestingly, in vivo studies observe that the two replication forks remain fastened together, often referred to as a replication factory. Replication factories containing two replisomes are well documented in cellular studies of bacteria (Escherichia coli and Bacillus subtilis) and the eukaryote, Saccharomyces cerevisiae. This basic twin replisome factory architecture may also be preserved in higher eukaryotes. Despite many years of documenting the existence of replication factories, the molecular details of how the two replisome machines are tethered together has been completely unknown in any organism. Recent structural studies shed new light on the architecture of a eukaryote replisome factory, which brings with it a new twist on how a replication factory may function.